2018
DOI: 10.1002/anie.201806334
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Stereodefined Borylated Dendralenes through Copper‐Catalyzed Allylboration of Alkynes

Abstract: An efficient method to access diversely substituted borylated dendralenes from simple and readily available materials is reported. This method is based on a multicomponent copper-catalyzed allylboration of alkynes with diboron and a 1,4-dibromo-2-butene which provides bromo- and boron-substituted skipped dienes with a remarkable chemo-, stereo-, and regioselectivity. These products can be easily transformed into dendralenic organoboronates, which display an extremely versatile reactivity as demonstrated by nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 85 publications
0
22
0
Order By: Relevance
“…At the outset of our studies, we focused on creating an enantioselective variant of the coupling of alkynes, diboron compounds, and 1,4‐dihalo‐2‐butenes that we had recently published . After surveying the performance of several chiral ligands in the reaction between phenylacetylene ( 1 ), 1,4‐dibromo‐2‐butene ( 2 ), and B 2 pin 2 , we found that the Cu complex derived from the sulfonate‐bearing NHC ligand L afforded 3 as a single isomer in 88 % yield, with an excellent 97:3 enantiomeric ratio and complete levels of regioselectivity (β‐borylation and S N 2′ allylation >99 %; Table , entry 1).…”
Section: Methodsmentioning
confidence: 99%
“…At the outset of our studies, we focused on creating an enantioselective variant of the coupling of alkynes, diboron compounds, and 1,4‐dihalo‐2‐butenes that we had recently published . After surveying the performance of several chiral ligands in the reaction between phenylacetylene ( 1 ), 1,4‐dibromo‐2‐butene ( 2 ), and B 2 pin 2 , we found that the Cu complex derived from the sulfonate‐bearing NHC ligand L afforded 3 as a single isomer in 88 % yield, with an excellent 97:3 enantiomeric ratio and complete levels of regioselectivity (β‐borylation and S N 2′ allylation >99 %; Table , entry 1).…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported a catalytic methodology that allows the synthesis of borylated dendralenes from readily available alkynes, 1,4‐dibromo‐2‐butene and B 2 pin 2 [11] . As part of our studies on the functionalization of this new type of organoboronates, [11, 12] we attempted to transform 1 into methyl‐substituted dendralene 2 through a Zweifel coupling which would involve boronate complex formation, 1,2‐metallate rearrangement and deiodoborylation [13] . Surprisingly, when 1 was sequentially treated with 1 equiv of MeLi and iodine, no tractable amount of Zweifel coupling product 2 was detected.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported a catalytic methodology that allows the synthesis of borylated dendralenes from readily available alkynes, 1,4-dibromo-2-butene and B 2 pin 2 . [11] As part of our studies on the functionalization of this new type of organoboronates, [11,12] we attempted to transform 1 into methylsubstituted dendralene 2 through a Zweifel coupling which would involve boronate complex formation, 1,2-metallate rearrangement and deiodoborylation. [13] Surprisingly, when 1 was sequentially treated with 1 equiv of MeLi and iodine, no tractable amount of Zweifel coupling product 2 was detected.…”
mentioning
confidence: 99%